Combination of polycarboxybetaine coating and factor XII inhibitor reduces clot formation while preserving normal tissue coagulation during extracorporeal life support. (May 2021) - Naito, Noritsugu; Ukita, Rei; Wilbs, Jonas; Wu, Kan; Lin, Xiaojie; Carleton, Neil M.; Roberts, Kalliope; Jiang, Shaoyi; Heinis, Christian; Cook, Keith E.
Abstract: Blood contact with high surface area medical devices, such as dialysis and extracorporeal life support (ECLS), induces rapid surface coagulation. Systemic anticoagulation, such as heparin, is thus necessary to slow clot formation, but some patients suffer from bleeding complications. Both problems might be reduced by 1) replacing heparin anticoagulation with artificial surface inhibition of the protein adsorption that initiates coagulation and 2) selective inhibition of the intrinsic branch of the coagulation cascade. This approach was evaluated by comparing clot formation and bleeding times during short-term ECLS using zwitterionic polycarboxybetaine (PCB) surface coatings combined with either a potent, selective, bicyclic peptide inhibitor of activated Factor XII (FXII900) or standard heparin anticoagulation. Rabbits underwent venovenous ECLS with small sham oxygenators for 60 min using three means of anticoagulation (n = 4 ea): (1) PCB coating + FXII900 infusion, (2) PCB coating + heparin infusion with an activated clotting time of 220–300s, and (3) heparin infusion alone. Sham oxygenator blood clot weights in the PCB + FXII900 and PCB + heparin groups were 4% and 25% of that in the heparin group (p < 10 −6 and p < 10 −5 ), respectively. At the same time, the bleeding time remained normal in the PCB + FXII900 group (2.4 ± 0.2 min) but increased to 4.8 ± 0.5 and 5.1 ± 0.7 min in the PCB + heparin and heparin alone groups (p < 10 −4 and 0.01). Sham oxygenator blood flow resistance was significantly lower in the PCB + FXII900 and PCB + heparin groups than in the heparin only group (p < 10 −6 and 10 −5 ). These results were confirmed by gross and scanning electron microscopy (SEM) images and fibrinopeptide A (FPA) concentrations. Thus, the combined use of PCB coating and FXII900 markedly reduced sham oxygenator coagulation and tissue bleeding times versus the clinical standard of heparin anticoagulation and is a promising anticoagulation method for clinical ECLS.